2006
DOI: 10.1029/2005gl025278
|View full text |Cite
|
Sign up to set email alerts
|

Dust events in Kanpur, northern India: Chemical evidence for source and implications to radiative forcing

Abstract: [1] Dust samples were collected and analyzed during May 2004 in Kanpur (in Ganga basin), Northern India for the first time. Chemical evidence along with the air mass trajectories suggests three major sources of the mineral dusts transported to the Ganga basin. High concentration of Pb and Cd indicates possible mixing with the anthropogenic pollution. The composite aerosol model reveals low single scattering albedo ($0.74) due to the presence of black carbon. During the dust storms, shortwave (SW) clear-sky diu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 13 publications
6
96
0
Order By: Relevance
“…Such a coexistence of mineral dust and high pollution levels in Beijing is confirmed by the yearly particle analysis of Zheng et al (2005). Similar conditions are also reported for Kanpur by Chinnam et al (2006). Alta Floresta, a site characterized by high biomass burning, provides a nice example of cloud contamination: the whole dataset shows a very coherent fine mode of 0.10-0.13 µm with concurrent increase in AOT and coarse mode fraction taking place exactly along the constant R f curves.…”
Section: Application To Aeronet Datasupporting
confidence: 79%
“…Such a coexistence of mineral dust and high pollution levels in Beijing is confirmed by the yearly particle analysis of Zheng et al (2005). Similar conditions are also reported for Kanpur by Chinnam et al (2006). Alta Floresta, a site characterized by high biomass burning, provides a nice example of cloud contamination: the whole dataset shows a very coherent fine mode of 0.10-0.13 µm with concurrent increase in AOT and coarse mode fraction taking place exactly along the constant R f curves.…”
Section: Application To Aeronet Datasupporting
confidence: 79%
“…Ho et al (2007) have observed significantly lower oxalic acid concentrations for the summer season as compared to winter in a study conducted over 14 Chinese cities. Over the northern part of Indian subcontinent high dust loading rich in mineral aerosols (especially iron content) has been reported during the summer season (Chinnam et al, 2006 and references therein). also reported a similar depletion of oxalic acid relative to other diacids in Arctic aerosols during the polar sunrise (spring season).…”
Section: Concentrations Of Total Diacids Overmentioning
confidence: 99%
“…In the Indian sub-continent, a positive aerosol forcing has been reported by several authors, e.g., at Kanpur in the Indo-Gangetic (IG) basin (Chinnam et al, 2006, Dey andTripathi, 2008), in the wintertime at Manora Peak in the Published by Copernicus Publications on behalf of the European Geosciences Union. 11210 G. P. Gobbi et al: Sunphotometry 2006 at the Himalayan EvK2-CNR station (5079 m a.s.l.)…”
Section: Introductionmentioning
confidence: 98%